2015
DOI: 10.1556/2006.4.2015.005
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of phubbing, which is the sum of many virtual addictions: A structural equation model

Abstract: Background and AimsPhubbing can be described as an individual looking at his or her mobile phone during a conversation with other individuals, dealing with the mobile phone and escaping from interpersonal communication. In this research, determinants of phubbing behavior were investigated; in addition, the effects of gender, smart phone ownership and social media membership were tested as moderators.MethodsTo examine the cause–effect relations among the variables of the theoretical model, the research employs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
370
6
91

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 330 publications
(496 citation statements)
references
References 64 publications
(100 reference statements)
29
370
6
91
Order By: Relevance
“…As such, it was decided that the criterion 'using a smartphone instead of actively participating in an on-going discussion being had by one's surrounding peers' should be used to include students into the study group. In the second step, the Phubbing Scale (Karadağ et al, 2015), a 5-point Likert scale composed of a total of 10 items measuring (i) Communication Disorders (5 items; α = .87) and (ii) Telephone Obsession (5 items; α = .85), was used. A score of 40 or more indicated an addiction to phubbing.…”
Section: Methodsmentioning
confidence: 99%
“…As such, it was decided that the criterion 'using a smartphone instead of actively participating in an on-going discussion being had by one's surrounding peers' should be used to include students into the study group. In the second step, the Phubbing Scale (Karadağ et al, 2015), a 5-point Likert scale composed of a total of 10 items measuring (i) Communication Disorders (5 items; α = .87) and (ii) Telephone Obsession (5 items; α = .85), was used. A score of 40 or more indicated an addiction to phubbing.…”
Section: Methodsmentioning
confidence: 99%
“…El término phubbing surge de la unión de las palabras "phone" (teléfono) y la palabra "snubbing" (des-preciar). Según Karadag et al (2015), el phubbing consiste en el acto de menospreciar o ignorar a quien nos acompaña al prestar mayor atención a nuestro celular (smartphone). En el caso del phubbing en la pareja, se refiere a cómo una persona percibe que su pareja lo menosprecia o ignora por estar prestando más atención a su celular (smartphone).…”
Section: Uso Del Celularunclassified
“…• Social Media Addiction and Phubbing Karadağ et al (2015) found that social media addiction has a great effect on phubbing behavior, and this is also related to the Internet addiction since social media functions through the Internet connection. Smartphone addiction is also seen as similar to the Internet addiction (Mok et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%